Facilitating reflective practice: developing built environment educators’ capacity for teaching and learning - Ruge, Gesa; Mackintosh, L. (2020)
The international literature on higher education emphasises the importance for academics and professional staff to develop their disciplinary teaching and learning practice. Teaching staff in built environment degree programs tend to focus on ‘what’ subject content is taught and less on ‘how to’ improve and innovate teaching and learning contexts and students’ skills development. To investigate these trends, this research reviewed the higher education literature and relevant international studies on strategies to enhance quality teaching and student learning. Findings highlight that reflective practice and engaging in a personal teaching philosophy and teaching profile provide an important link for individual professional development and basis for improving teaching and learning. The objective of this study was to apply findings from the literature in facilitating professional learning workshops, with a pedagogy for collaborative reflective practice and the development of a teaching philosophy. This research reports on the first stage of professional development for staff in built environment programs to establish a teaching profile through reflection on their personal and discipline specific pedagogies. Initial findings highlight the positive impact of reflection and collegial conversations about learning and teaching, as well as future opportunities for individual and discipline based capacity building for improving educational practice.